Significance of the Dead Sea scrolls and other essays : Biblical and early Christianity studies from Malawi - Nkhoma, Jonathan S. (Mzuni books, 2013)
The author, in this scholarly collection of essays, enriches the reader with different interesting windows on how one can unearth the riches contained in some of the New Testament writings. The first two essays underscore the importance of placing the New Testament in a proper context and attempt to construct this context by discussing the historical background and the theological understanding of the Qumran Covenanters as derived from the Dead Sea Scrolls. The author treats many aspects touching the proper interpretation of the New Testament writings. For example, he shows how the sacramental rituals of washing and eating together in the Qumran Community add meaning to the same rituals carried over to the New Testament. The significance of table fellowship is treated in greater depth in a subsequent essay. Throughout the various essays, the question of the historicity of the various texts is treated in a succinct way and the author is able to come to some helpful conclusions drawing on the previous work of many well-known scholars. The later essays tackle the very difficult question of martyrdom, and the author delves into the history of two particular cases in order to shed light on this difficult subject.